2019
DOI: 10.1111/iej.13108
|View full text |Cite
|
Sign up to set email alerts
|

Penetration depth of irrigants into root dentine after sonic, ultrasonic and photoacoustic activation

Abstract: Aim To compare penetration depths of endodontic irrigants into the dentinal tubules of extracted teeth when using several activation methods. Methodology The root canals of 90 extracted human teeth were prepared to size 40, .06 taper. The straight and round‐shaped root canals were distributed randomly into six groups, and final irrigation was performed with EDTA and sodium hypochlorite as follows: (I) manual dynamic activation, (II) Ultrasonic, (III) Sonic, (IV) PIPS (photon‐induced photoacoustic streaming, (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
90
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 31 publications
7
90
0
9
Order By: Relevance
“…In this study, NaOCl infiltration was consistently lower apically when compared to the corresponding coronal and middle segments, where there was relatively even penetration in both bucco‐lingual and mesio‐distal planes. Despite the use of different methodologies, similar observations have also been reported by Paqué et al (2006), Giardino et al (2017) and Galler et al (2019). This regional variation can be attributed to characteristic features of apical dentine, which include increased peritubular sclerosis that advances in a coronal direction from 30 years of age, as well as reduced tubular density (Mjör & Nordahl 1996, Mjör et al 2001, Paqué et al 2006).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, NaOCl infiltration was consistently lower apically when compared to the corresponding coronal and middle segments, where there was relatively even penetration in both bucco‐lingual and mesio‐distal planes. Despite the use of different methodologies, similar observations have also been reported by Paqué et al (2006), Giardino et al (2017) and Galler et al (2019). This regional variation can be attributed to characteristic features of apical dentine, which include increased peritubular sclerosis that advances in a coronal direction from 30 years of age, as well as reduced tubular density (Mjör & Nordahl 1996, Mjör et al 2001, Paqué et al 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have added fluorescent dyes to irrigants for subsequent confocal laser scanning microscopy analysis (Llena et al 2015, Vadhana et al 2015, Gu et al 2017). Others have substituted NaOCl completely for fluorescent solutions, which have then been viewed under a light microscope (Galler et al 2019). These approaches were not employed here as the oxidizing nature of NaOCl could affect the fluorescent capacity of the dye and surrogate solutions may not have the same penetrative properties as the test irrigant.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, among the four different irrigation techniques, no significant differences were observed in the investigated parameters in relation to sealer penetration. While these findings align well with some of the earlier studies [7,9], the results of other studies in a review of the literature were found to be contrasting [10,11,13,[33][34][35]. Galler et al [34] found greater penetration depths in the apical thirds for ultrasonic and sonic activation groups compared to MDA.…”
supporting
confidence: 88%
“…While these findings align well with some of the earlier studies [7,9], the results of other studies in a review of the literature were found to be contrasting [10,11,13,[33][34][35]. Galler et al [34] found greater penetration depths in the apical thirds for ultrasonic and sonic activation groups compared to MDA. Barbosa et al [35] reported that the ultrasonic activation provides better penetration of the sealer than MDA did.…”
supporting
confidence: 88%
“…Recent in vitro studies have shown that, compared with manual irrigation, the sonic irrigation device EDDY improves the dentin debris removal from artificial canal irregularities [14], the removal of calcium hydroxide from artificial grooves in the root canal of maxillary incisors [9], the removal of remnants of sealer and guttapercha [15] and the median dye penetration depths in dentinal tubules of apical root sections [16]. However, considering the pivotal etiopathogenetic role of endodontic biofilms in periapical disease, the reduction of the microbial load within root canal systems is arguably the most relevant surrogate marker in experimental irrigation studies [17].…”
Section: Discussionmentioning
confidence: 99%